PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN WAJIB DI INDONESIA - Suhardjanto, Djoko; Lesmana, Sigit Indra (PRESTASI, 2010)
AbstractThe objective of this research is to investigate the influence of local government charachteristics to mandatory disclosure compliance. Characteristics of local governments are identified as size of local government, debt, intergovernmental revenue, the age of local government, the number of functional differentiation and independence of financial ratio. Mandatory disclosure compliance is measured by 46 items based on governmental accounting standards.This study uses purposive sampling method. The sample consists of 79 Inddonesian local government financial reports of the year 2007. The statistical analysis use descriptive statistics and multiple regression. Results show that Indonesian local government has low level in mandatory disclosure of 22 %. From the regression analysis can be concluded that the age of local government and independence of financial ratio is good predictor for mandatory disclosure compliance. Keywords:Â Local governmental characteristics, mandatory disclosure, governmental accounting standards